Modelling of treatment while preparation of thread-grinding of hard spiral surphaces at the example of a ring treatment with a M210 х 3 methric thread - Gazizov A. F. (Innovative technologies in science and education, 2016)
in this article the calculation of thread-machine adjustments and tool parameters for processing the internal thread by grinding method. It is shown that thread grinding with the required accuracy can be performed without tilting the tool spindle.
Keywords: внутренняя резьба; резьбошлифование; моделирование обработки; расчет наладки; межосевой угол; inner thread; thread-grinding; treatment modelling; adjustment calculation; interaxle angle